Soy oil and SPI based-oleogels structuring with glycerol monolaurate by emulsion-templated approach: Preparation, characterization and potential application. (15th December 2022) - Zou, Yucheng; Xi, Yuhang; Pan, Jingjing; Ijaz Ahmad, Muhammad; Zhang, Aiping; Zhang, Cen; Li, Yang; Zhang, Hui
Highlights: Soybean oil-based oleogels were gelled by soy protein isolate/glycerol monolaurate. Oleogels caused a compact 3D network structure and intermolecular hydrogen bonds. Oleogels showed the enhanced oil bonding capacity and physical stability. Oleogels with complex gelators had higher oil digestion rates. Abstract: In this study, soybean oil-based oleogels were prepared using soy-protein isolate (SPI) and glycerol monolaurate (GML) in an emulsion-template approach. The rheological, texture, microstructure, and oil-retention properties of the obtained oleogels were analyzed. Results showed that the soy oil-based oleogel prepared with 6 wt% GML exhibited high oil loss, low-hardness, and needle-like morphology compared to the soy-oil/SPI-based oleogel. On the other hand, soy oil-based /SPI-based oleogels structured by 3 or 6 wt% GML presented moderate thermal-stability and lowest oil loss than those prepared without GML. Furthermore, SPI-based oleogel containing 6 wt% GML showed highest free fatty acids release (62.07%) with significantly improved elastic modulus and apparent viscosity. Additionally, the obtained oleogels displayed the occurrence of van der Waals interactions and intermolecular hydrogen bonds, presenting enhanced thermal stability. These results contribute to a better understanding of oleogelation-based emulsions for formulating trans -free and low-saturated foodstuffs with desired physical and functional properties.